Evaluation of Rocuronium Continuous Infusion in Critically Ill Patients During the COVID-19 Pandemic and Drug Shortages. (April 2023) - Aldhaeefi, Mohammed; Dube, Kevin M.; Kovacevic, Mary P.; Szumita, Paul M.; Lupi, Kenneth E.; DeGrado, Jeremy R.
Background: Limited data exist to support the use of rocuronium continuous infusions in the intensive care unit (ICU).Objective: To evaluate the dosing and monitoring of adult patients who received rocuronium for hypoxemic respiratory failure during the Coronavirus Disease 2019 (COVID-19) pandemic.Methods: This was a retrospective, single-center study from March 1, 2020 to May 31, 2020. We identified all adult patients admitted to any ICU who received rocuronium via continuous infusion. Patients were excluded if they received rocuronium for <6 hours. The main outcome of this study was to determine the median rocuronium maintenance continuous infusion rate in the ICU. Secondary outcomes of this study included the initial continuous infusion rate, duration of therapy, cumulative dose, frequency and median of rocuronium boluses, time to resolution of neuromuscular blockade, and the relationship between the hourly administration rates of rocuronium and train-of-four (TOF) assessments.Results: Seventy-one patients and 97 paralytic infusions were included. Fifty-nine patients (83%) were positive for SARS CoV-2. Of the 97 rocuronium infusions, the median dose at initiation was 3 (3–5) mcg/kg/min and duration of infusion was 45 (23.6–92.5) hours. The median continuous infusion maintenance rate was 4.3 (2.8–7.2) mcg/kg/min. There was a negligible correlation between the dose of rocuronium and the TOF results (r = .04). A total of 1775 TOFs were assessed, of which 46.2% were over-paralyzed, 35.7% well-paralyzed, and 18.1% under-paralyzed.Conclusions: The initial and maintenance infusion doses in our analysis were lower than what have been previously referenced.